Designing and Using Esp Self Access Materials in the SBI Context - Rifai, Irfan (Bina Nusantara University, 2010)
Article presented the design and utility of ESP materials which were self – accessible for the SBI students which required careful thoughts and preparations. The study began by determining the students’ needs of ESP, continued by the course developer who collected the required materials from four different source, those are published materials, authentic material, self-made materials and materials from students’ contributions. The use of the materials were still needed the active role of teachers in setting visiting time, counseling or even assessing students’ works. It is concluded that the less autonomous nature of the self access context for the SBI context is based on the assumption that younger students still require guidance and supervision from their teachers.